Implementasi Metode Fuzzy Black-Scholes Real Options Valuation pada Rencana Investasi Smelter Nikel - Jalaludin, Paiz; Rahman, Alrafiful; Andirasdini, Indah Gumala (KUBIK, 2023)
Indonesia is the largest nickel producing country in the world in 2022 by contributing 48.48% of the world's total nickel production. Therefore, the Indonesian government pays attention to the development of smelter companies by planning to build around 53 companies in 2024, and 56.60 percent of them are nickel smelters. The potential of the nickel smelter needs attention from various circles, especially academics from various disciplines. One that needs attention is the study of the method of evaluating the economic value of the investment plan in the nickel smelter company. The DCF method, although practical and widely used, still has a drawback, which is that it does not pay attention to the flexibility of managers' decision-making in the middle of the ongoing investment period. As a solution, the real options valuation (ROV) method provides flexibility features in making these decisions. Among the real options methods that are often used is the Black-Scholes formula which is considered the most rigid but more practical real options method. However, this problem can be overcome by implementing the fuzzy number method into the ROV method, making it more flexible. The results of this study show that the fuzzy Black-Scholes ROV method is a practical method, can calculate the risks and projects flexibility, and become a solution when initial information is less available about the characteristics of nickel smelter investment projects.